Chemical Composition of the Essential oil of Satureja bachtiarica Bunge. from Iran - Mahmoodreza Moein,; Forough Karami,; Hossein Tavallali,; Younes Ghasemi, (Iranian Journal of Pharmaceutical Sciences, 2012)
Due to various usages of Satureja species or their oils, we were interested in studying essential oil contents and compositions of Satureja species in Iran. So, the essential oil of aerial parts of Satureja bachtiarica Bunge. growing in Iran was obtained by hydrodistillation and was analyzed by GC-MS. Twenty eight compounds constituting 99.80% of the oil were identified and yield of the oil was 2.7% (V/W). The major components were found to be thymol (65.1%), γ-terpinene (15.0%), β-caryophyllene (4.85%), p-cymene (4.4%), linalool (3.5%) and borneol (3.05%).